2018
DOI: 10.4314/ahs.v18i4.44
|View full text |Cite
|
Sign up to set email alerts
|

Levels of heavy metals in urine samples of school children from selected industrial and non-industrial areas in Dar es Salaam, Tanzania

Abstract: ObjectivesThe levels of lead, zinc, iron, copper and cadmium metals in the urine samples of selected school children in industrial and non-industrial areas in Dar es Salaam were investigated.MethodsUrine samples were collected from 120 children in industrial areas and 120 children in non-industrial areas then digested in concentrated acids and analysed using atomic absorption spectrophotometry (AAS).ResultsThe concentrations of the heavy metals in the urine samples ranged from below detection limit/non-detecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 15 publications
0
15
0
2
Order By: Relevance
“…A total of 26 studies measured urinary zinc in infants and children aged 0 to 9 years. [48][49][50][51]54,57,60,[62][63][64][67][68][69][70][71]74,[76][77][78][79][82][83][84][85][86][87] Of these, 14 provided data from children aged 0 to 3 years [48][49][50]54,57,60,67,71,73,74,77,84,86,87 and 13 provided data from children aged 4.5 to 9 years. 48,51,[62][63][64][68][69][70]76,79,82,…”
Section: Data Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 26 studies measured urinary zinc in infants and children aged 0 to 9 years. [48][49][50][51]54,57,60,[62][63][64][67][68][69][70][71]74,[76][77][78][79][82][83][84][85][86][87] Of these, 14 provided data from children aged 0 to 3 years [48][49][50]54,57,60,67,71,73,74,77,84,86,87 and 13 provided data from children aged 4.5 to 9 years. 48,51,[62][63][64][68][69][70]76,79,82,…”
Section: Data Synthesismentioning
confidence: 99%
“…Tables S1 and S3 in the Supporting Information provide descriptions of these studies, with Table S1 detailing studies excluded from the metaanalyses and Table S3 detailing studies included in the meta-analyses. Urinary zinc was measured by atomic absorption spectrometry, 48,49,51,54,60,[62][63][64]68,69,71,74,[76][77][78][79]82,84,86,87 a colorimetric method, 50,67 inductively coupled plasma-atomic emission spectrophotometry, 85 inductively coupled plasma mass spectrometry, 70 and liquid chromatography. 83 Three studies assessed zinc excretion from spot urine samples.…”
Section: Data Synthesismentioning
confidence: 99%
“…The most informative or diagnostic biosubstrates are those that are involved in the processes of transport, excretion, and accumulation of metals [ 1 , 3 , 8 ]. In population-based studies, human hair (nails), blood (whole or serum), and urine (morning or daily) are usually used as such diagnostic biosubstrates.…”
Section: Introductionmentioning
confidence: 99%
“…Workers such as Mahugija et al have reported high contamination levels of heavy metals in urine samples of school children from selected industrial and non-industrial areas in Tanzania [10]. Similarly, Sá et al investigated the presence and distribution of heavy metals in samples of renal cell carcinoma, as well as adjacent renal tissue (control samples) in patients submitted to radical or partial nephrectomy for renal cell carcinoma [11].…”
Section: Introductionmentioning
confidence: 99%